Face to Face with the Financial Crisis: The U.S. Presidential Election from a Transnational Perspective - Amelie Constant; Klaus F. Zimmermann (Weekly Report, 2008)
Much work awaits the new U.S. president. The U.S. has been financially depletedby the Iraq war, economic programs and necessary financial system restructuringcosts. The current financial crisis requires a government that takes an active hand ineconomic matters; at the same time, however, the state cannot deny the role that itplayed in bringing about the current problem: the housing market bubble was abettedby financial politics; economic programs went up in smoke; and the fall of LehmanBrothers portended the beginning of a systemic worldwide crisis.Empirical data based on internet statistics for accessing searches suggest that thefinancial crisis is viewed as more significant in Germany than in the United States.Although both countries' interests in the credit crunch have recently decreased, fearsof a recession have increased. Americans, moreover, have demonstrated a heightenedconcern about unemployment. This emphasizes the central challenge of the new U.S.president: to secure more job opportunities for American citizens. If one is to believe theinternet statistics for accessing searches in both countries, Obama energized Germanyslightly more than he did the United States, though he still dominated McCain in bothcountries. The McCain-Palin ticket is still quite appealing, however, when viewed incomparison to Obama-Biden.
Keywords: 330